ChatGPT and Translanguaging in Presentation in English Class: Unveiling The utility In EFL Context In Indonesia - Alfiani, Syafira; Yuni Putri Utami; Lukman Hakim; Achmad faqih; Awati Fane (Jurnal Intelek Insan Cendikia, 2025)
This research aims to unveil a different reality regarding the utility of ChatGPT and translanguaging in presentations in English classes, focusing on their impact on students’ critical thinking and speaking skills when discussing specific engineering topics and acquiring a foreign language. By employing qualitative research, this study explores the phenomenon of using ChatGPT and translanguaging to enhance students’ critical thinking and speaking skills in depth. There are 10 participants from two departments: the Engineering Department and the English Language and Culture Department. All participants are fifth-semester students. The results found different outcomes of implementing translanguaging in an EFL classroom and using ChatGPT as a medium to support students’ ideas during discussions which in fact, it cannot boost their critical thinking due to overly depend on ChatGPT and other artificial tools. Data is collected through semi-structured interviews. The research gap addressed in this study is the lack of empirical evidence on the utility of translanguaging amidst rapid development ChatGPT in improving students' speaking skills and critical thinking in an EFL context.